Multiple pathogenic proteins implicated in neuronopathic Gaucher disease mice. (5th March 2014) - Xu, You-hai; Xu, Kui; Sun, Ying; Liou, Benjamin; Quinn, Brian; Li, Rong-hua; Xue, Ling; Zhang, Wujuan; Setchell, Kenneth D.R.; Witte, David; Grabowski, Gregory A.
Abstract: Gaucher disease, a prevalent lysosomal storage disease (LSD), is caused by insufficient activity of acid β-glucosidase (GCase) and the resultant glucosylceramide (GC)/glucosylsphingosine (GS) accumulation in visceral organs (Type 1) and the central nervous system (Types 2 and 3). Recent clinical and genetic studies implicate a pathogenic link between Gaucher and neurodegenerative diseases. The aggregation and inclusion bodies of α-synuclein with ubiquitin are present in the brains of Gaucher disease patients and mouse models. Indirect evidence of β-amyloid pathology promoting α-synuclein fibrillation supports these pathogenic proteins as a common feature in neurodegenerative diseases. Here, multiple proteins are implicated in the pathogenesis of chronic neuronopathic Gaucher disease (nGD). Immunohistochemical and biochemical analyses showed significant amounts of β-amyloid and amyloid precursor protein (APP) aggregates in the cortex, hippocampus, stratum and substantia nigra of the nGD mice. APP aggregates were in neuronal cells and colocalized with α-synuclein signals. A majority of APP co-localized with the mitochondrial markers TOM40 and Cox IV; a small portion co-localized with the autophagy proteins, P62/LC3, and the lysosomal marker, LAMP1. In cultured wild-type brain cortical neural cells, the GCase-irreversible inhibitor, conduritol B epoxide (CBE), reproduced the APP/α-synuclein aggregation and the accumulation of GC/GS. Ultrastructural studies showed numerous larger-sized and electron-dense mitochondria in nGD cerebral cortical neural cells. Significant reductions of mitochondrial adenosine triphosphate production and oxygen consumption (28–40%) were detected in nGD brains and in CBE-treated neural cells. These studies implicate defective GCase function and GC/GS accumulation as risk factors for mitochondrial dysfunction and the multi-proteinopathies (α-synuclein-, APP- and Aβ-aggregates) in nGD.